2017
DOI: 10.2147/rrn.s128751
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis and neonatal morbidity: current perspectives

Abstract: Abstract:The term chorioamnionitis (CA) is commonly used to refer to different clinical or pathological conditions characterized by an infectious and/or inflammatory process that affects primarily the chorioamniotic membranes, but also the amniotic fluid, vessels of the chorionic plate, and, eventually, the umbilical cord (funisitis) and the fetus. Its incidence is higher at lower gestational ages, and the main mechanism is believed to be the ascending bacterial infection from the maternal genital tract. It ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 128 publications
1
5
1
2
Order By: Relevance
“…We believe this aspect is also important to give a just and dutiful answer to the couple that suffered this dramatic event, which in our population occurred after 30 weeks of gestation in 72% of the cases, when the chances of newborn survival increase significantly with good intensive care, and after 36 weeks in 34% of cases, meaning at term. Some 88% of IUFD cases recorded in this study occurred in the antepartum period and this figure is in line with what was reported by other works carried out in high-income countries, where 90% of deaths in utero occur precisely in this period and are often associated with preventable risk factors, such as obesity, smoking, failure to identify pregnancies at risk [6,[27][28][29][30][31][32][33][34][35]. Therefore, being able to understand the cause of death in utero would allow addressing the available resources more appropriately to combat the etiological factors on which it is possible to implement concrete prevention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We believe this aspect is also important to give a just and dutiful answer to the couple that suffered this dramatic event, which in our population occurred after 30 weeks of gestation in 72% of the cases, when the chances of newborn survival increase significantly with good intensive care, and after 36 weeks in 34% of cases, meaning at term. Some 88% of IUFD cases recorded in this study occurred in the antepartum period and this figure is in line with what was reported by other works carried out in high-income countries, where 90% of deaths in utero occur precisely in this period and are often associated with preventable risk factors, such as obesity, smoking, failure to identify pregnancies at risk [6,[27][28][29][30][31][32][33][34][35]. Therefore, being able to understand the cause of death in utero would allow addressing the available resources more appropriately to combat the etiological factors on which it is possible to implement concrete prevention.…”
Section: Discussionsupporting
confidence: 91%
“…Consideration must be made on the high frequency of cases in which a condition of chorioamnionitis (11%) had occurred, a share that is certainly higher than the values reported in the literature for this pathology and that is usually estimated in the range of 1-4% [32,33]. Chorioamnionitis was defined by the association of clinical signs of maternal inflammation with fetal tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] The term intrauterine infection refers to different clinical or pathological conditions characterized by an infectious or inflammatory process that affects the chorioamniotic membranes, amniotic fluid, umbilical cord (funisitis), and eventually the fetus. [ 18 ] Intrauterine infection is one of the significant intrinsic causes of IUGR, since in intrauterine infection, the umbilical cord also gets infected which causes uteroplacental insufficiency which further reduces the transportation of nutrients and oxygen and ultimately results in poor fetal growth during pregnancy. [ 19 ] The findings that PROM has a significant adverse impact on neonatal birth weights and birth length by all gestational weeks, which indicate that it may be due to intrauterine infection of neonates, but unfortunately, we are missing the data regarding intrauterine infection in our study.…”
Section: Discussionmentioning
confidence: 99%
“…23 Amniyon kavitesi, normalde steril kabul edilmekle birlikte son yıllarda plasentanın kendine özgü florası olduğu da artık bilinmekte ve bu vajinal/servikal mikrobiyal floranın değişerek patolojik bakterinin ortaya çıkabileceği görüşü de ağırlık kazanmaktadır. [24][25][26][27][28] İNFLAMASYON NASIL OLUYOR?…”
Section: Patojen Bakteri̇leri̇n Geli̇ş Yoluunclassified
“…Fetal kortizol seviyesi yükselmekte ve bakteriler ve/veya onların endotoksinlerine yanıt olarak interlökin (IL)-1, IL-6, IL-8, tümör nekrozis faktör-α (TNFα), MMP gibi sitokin/kemokin artışı, lökosit adez-yon moleküllerinin upregülasyonu ile fetal sellüler ve humoral immün aktivasyonu ortaya çıkmaktadır. 9,24,[29][30][31][32]…”
Section: Fetal Evreunclassified